Formulasi dan Uji Aktivitas Sediaan Hair Tonic Kafein untuk Menstimulasi Pertumbuhan Rambut pada Hewan Uji Marmut - Aztriana Aztriana; Nurlina Nurlina; Dian Safitri Achmad; Vina Purnamasari; A Hasrawati (Journal of Pharmaceutical and Health Research, 2023)
Hair loss occurs in many people, so it can reduce the cosmetic function and protect the body and head from the environment. Hair loss is a disorder in which the number of hairs is less or more than normal. Hair tonic includes cosmetic preparations that have a liquid form with the function of maintaining hair health, stimulating hair growth, and strengthening hair. Caffeine is a substance that can stimulate hair growth. The purpose of this study was to determine the activity of a hair tonic preparation containing caffeine that can stimulate hair growth in guinea pigs. The results showed that hair tonic caffeine Formula 1 with a concentration of 0.001% with an average hair length of 18.294 mm had high effectiveness in stimulating hair growth compared to Formula 2 with a concentration of 0.005% with an average hair length of 16.610 mm.